2019
DOI: 10.1111/jgh.14777
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial profile in biliary atresia: a case‐control study

Abstract: Background and Aim Biliary atresia (BA) is a progressive fibro‐inflammatory cholangiopathy with an unclear etiology. Various liver disorders are associated with an altered microbiome. However, gut microbiome in BA remains unknown. Here, we performed a case‐control study to investigate the gut microbiota in BA. Methods A cross‐sectional analysis was first conducted for 34 BA patients and 34 healthy controls. Then we investigated the shift in gut microbiota 2 weeks after the Kasai procedure in 16 BA patients. Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…In this study, the alpha diversity between BA patients and controls was comparable. Wang et al ( 11 ), who included 34 BA patients and 34 controls, have previously showed that alpha diversity in BA patients was significantly lower compared with that of controls. It might be that our sample size was too small to detect such significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the alpha diversity between BA patients and controls was comparable. Wang et al ( 11 ), who included 34 BA patients and 34 controls, have previously showed that alpha diversity in BA patients was significantly lower compared with that of controls. It might be that our sample size was too small to detect such significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the microbiota differed significantly: BA was associated with lower abundances of Actinobacteria (eg, Bifidobacteriaceae), the family Lachnospiraceae and greater abundances of Firmicutes (eg, Streptococcaceae), 3 families, which had been associated with BA previously ( 11 ). Bifidobacteriaceae, such as Bifidobacterium longum and Bifidobacterium adolescentis, are abundant anaerobic bacteria in the microbiota of healthy infants ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is termed the gut-liver axis. The gut-liver axis has also been investigated in BA (145). As MMP- 7 has not yet been identified in human intestinal Paneth cells, we will not discuss MMP-7 and the gut-liver axis in relation to BA here.…”
Section: Inflammation and Angiogenesismentioning
confidence: 99%
“…Pediatric patients with end-stage liver diseases, such as due to biliary atresia or other cholestatic diseases, often have an altered microbial composition (Guo et al 2018;Wang et al 2020a;Wang et al 2019). Such alteration in the microbiome would possibly lead to gut barrier disruption, to bacterial translocation and to triggering of the host's immune and metabolic responses in the liver (De Minicis et al 2014;Fouts et al 2012).…”
Section: Altered Microbial Composition/function In Patients Undergoing Ltmentioning
confidence: 99%
“…Such alteration in the microbiome would possibly lead to gut barrier disruption, to bacterial translocation and to triggering of the host's immune and metabolic responses in the liver (De Minicis et al 2014;Fouts et al 2012). For instance, infants with biliary atresia have lower microbial diversity and higher intestinal permeability than healthy infants (Wang et al 2020a). In particular, patients showed a decrease in the relative abundance of genera which are considered beneficial, i.e., Bifidobacterium and Faecalibacterium (Guo et al 2018;Wang et al 2019), as well as an imbalance in the components of bile acids (Wang et al 2019).…”
Section: Altered Microbial Composition/function In Patients Undergoing Ltmentioning
confidence: 99%